Transforming Financial Outsourcing Services for Sustainable Business Development: A Review on Green Finance - Laktionova, Olga; Kovalenko, Yuliia; Myhovych, Tetiana; Zharikova, Olena (Dr. Viktor Koval, 2022)
Introduction. Financial outsourcing services contribute to the effective management of economic relations arising in the process of the formation and use of financial resources. With the unchanged goal of financial outsourcing, its services are being transformed, associated with the development of the financial market and the emergence of innovative financial instruments, technologies and mechanisms. Aim and tasks. The purpose of the article is to form a methodology for studying financial markets, growth points and development trends of "green" finance and tools for sustainable business development that require the transformation of financial outsourcing services. Results. A review of sustainable business development based on the methodology of researching the green financial market and financial instruments was carried out, which consists in the use of biometric, predictive, and other methods of analysis that allow timely identification of innovative financial instruments, their development trends, empirical data on their significance, sources of funding, scale, models and trends in the development of economic relations arising in the process of environmental modernization of production. The proposed methodology for researching the financial market will make it possible to transform financial outsourcing services in a timely manner, especially for clients engaged in the development and implementation of engineering innovations aimed at developing a sustainable economy based on green finance. Conclusions. The dynamics of the development of green bonds is significantly ahead of the dynamics of the development of the financial market as a whole. The concept of organizing regional sustainable financial systems is proposed, the infrastructure of which includes a financial outsourcer that contributes to the effective attraction and use of financial resources for sustainable business development. A classification of client groups of financial outsourcing services is proposed depending on the size of business entities and the involvement of specific financial instruments and management mechanisms carried out by an outsourcer, which provides capital management using financial management mechanisms, accelerating its turnover and reuse.